REFLEKSI VARIASI FONOLOGIS PADA FONEM BAHASA ARAB MESIR DAN ARAB SAUDI - Darsita Suparno (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This article describes the type of phonological changes in Arabic everyday language pattern of Egypt and Saudi Arabia. The data collection was done by interview using Swadesh vocabulary as a guide. Each vocabulary was recorded and transcribed phonetically. From the comparison of sounds and phonemes forming vocabulary in both languages, known sound-changes of sound are classified, namely: (1) referential, (2) articulatory phonetics, (3) translational, (4) orthographic, (5) the tools of speech. Similarity technique is used to see similarities and differences. The results showed that everyday language pattern of Egypt and Saudi Arabia has a lot of phonological variation in the form of (a) lenition (b) deletion, (c) the addition of sound. The sound addition includes the addition of a consonant and vowel at the beginning, middle, and the end of the word. Sound deletion occurs at the beginning, in the middle and at the end of the word.